2016
DOI: 10.1002/med.21402
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies and Pharmacological Tools Influencing S1P Signaling and Metabolism

Abstract: During the last two decades the study of the sphingolipid anabolic, catabolic, and signaling pathways has attracted enormous interest. Especially the introduction of fingolimod into market as first p.o. therapeutic for the treatment of multiple sclerosis has boosted this effect. Although the complex regulation of sphingosine-1-phosphate (S1P) and other catabolic and anabolic sphingosine-related compounds is not fully understood, the influence on different (patho)physiological states from inflammation to cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 474 publications
(533 reference statements)
0
18
0
Order By: Relevance
“…Sphingolipids are integral components of cell membranes in the regulation of fluidity and lipid bilayer composition, organizing the assembly of signaling molecules, and protein trafficking. Particularly, some sphingolipids like sphingosine (Sph), sphingosine-1-phosphate (S1P), and ceramide (Cer) also act as bioactive signaling molecules and are responsible for the regulation of cell growth, differentiation, senescence, or apoptosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sphingolipids are integral components of cell membranes in the regulation of fluidity and lipid bilayer composition, organizing the assembly of signaling molecules, and protein trafficking. Particularly, some sphingolipids like sphingosine (Sph), sphingosine-1-phosphate (S1P), and ceramide (Cer) also act as bioactive signaling molecules and are responsible for the regulation of cell growth, differentiation, senescence, or apoptosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past two decades identified S1P as a potent bioactive lipid molecule that regulates various cellular processes including cell growth, apoptosis, immune regulation, etc. (49). …”
Section: Introductionmentioning
confidence: 99%
“…Other approaches have also been employed to manipulate S1P activity including targeting SphKs to control S1P synthesis. 3, 3537 There are currently multiple reports of potent SphK1-selective inhibitors and SphK1/SphK2-dual inhibitors (Figure 1). Inhibitors such as the SphK1-selective inhibitor 1 (PF-543) 38, 39 and the SphK1/SphK2-dual inhibitor 5 (SKI-II) 40–42 have been co-crystallized with SphK1 and have been useful in developing next generation inhibitors.…”
Section: Introductionmentioning
confidence: 99%